2008
DOI: 10.1093/jxb/ern132
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and expression analysis of the Rab GTPase family in Vitis vinifera reveal the specific expression of a VvRabA protein

Abstract: As a first step to investigate whether Rab GTPases are involved in grape berry development, the Vitis vinifera EST and gene databases were searched for members of the VvRab family. The grapevine genome was found to contain 26 VvRabs that could be distributed into all of the eight groups described in the literature for model plants. Genetic mapping was successfully performed; VvRabs were mostly located on independent chromosomes, apart from eight that were located on the as yet unassigned portions of the genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 39 publications
2
21
0
Order By: Relevance
“…The main changes occurring during fruit development are mediated by proteins transported through the cell endomembrane system and organelles, or secreted to the apoplast, indicating that GTPase is associated with development and if inhibited can cause physiologic disturbances (Abbal et al 2008). The higher expression of GTPase induced by GA 3 in woolliness free peaches is another evidence for the involvement the endomembrane trafficking favoring transport and recycling of proteins associated with cell wall and organelle biogenesis (González-Agüero et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…The main changes occurring during fruit development are mediated by proteins transported through the cell endomembrane system and organelles, or secreted to the apoplast, indicating that GTPase is associated with development and if inhibited can cause physiologic disturbances (Abbal et al 2008). The higher expression of GTPase induced by GA 3 in woolliness free peaches is another evidence for the involvement the endomembrane trafficking favoring transport and recycling of proteins associated with cell wall and organelle biogenesis (González-Agüero et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…However, numerous studies have reported that the transcript quantity of the most commonly used reference genes can vary considerably under different developmental, physiological and experimental conditions [11,15-23]. Several reference genes are commonly used, such as elongation factor [24,25], actin [26,27], ubiquitin [28,29], and ribosomal units (18S or 28S rRNA) [30-32]. However, several reports have demonstrated that transcript levels of these genes also vary considerably under different experimental conditions and consequently their suitability for gene expression studies must be evaluated case by case [22,33,34].…”
Section: Introductionmentioning
confidence: 99%
“…inhibitory factors in the sample, RNA integrity, and enzyme or primer performance (Bustin 2002;Fleige et al 2006;Fluck et al 2005)]. Several reference genes are commonly used, such as actin (Fung et al 2008;Ruan and Lai 2007), ubiquitin (Lund et al 2008;Olsen et al 2010), elongation factor (Abbal et al 2008;Olsen et al 2010). The ribosomal units (18S or 28S rRNA) (Bas et al 2004;Wang et al 2010;Xue et al 2010) are also frequently used.…”
Section: Introductionmentioning
confidence: 99%
“…Cabernet Sauvignon berries including elongation factor 1-(EF1-) and actin (ACT1) genes. Both of them, together with the 18S rRNA, have often been used as internal control genes to study grapevine gene expression (Abbal et al 2008;Fung et al 2008;Gao et al 2010;Hren et al 2009;Polesani et al 2008;Terrier et al 2005) although the stability of their expression has not been checked in conditions diVerent from those of Reid et al (2006). In particular, no validation of reference genes has been reported for grapevine samples in the context of plant-pathogen interaction until now.…”
Section: Introductionmentioning
confidence: 99%